Effects of Peripheral Vestibular Dysfunction on Dynamic Postural Stability Measured by the Functional Reach Test and Timed Up and Go Test. (June 2017) - Nishi, Toshiko; Kamogashira, Teru; Fujimoto, Chisato; Kinoshita, Makoto; Egami, Naoya; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Objective: To investigate the influence of vestibular function on dynamic postural stability assessed by the functional reach test (FRT) and the timed up and go test (TUG). Study design: Retrospective study. Setting: Tertiary referral center. Subjects and Methods: The FRT and TUG were performed in 399 patients with dizziness. The effects of peripheral vestibular dysfunction assessed by the caloric test and cervical vestibular evoked myogenic potentials (cVEMPs) to air-conducted sound (500 Hz, tone burst) on the results of FRT and TUG were analyzed. Results: Neither FRT nor TUG scores showed significant differences in relation to the results of the caloric test ( P > .3). The FRT scores in patients who showed abnormal cVEMP responses on both sides were significantly smaller than those in patients who showed normal cVEMP responses ( P < .01). The TUG scores in patients who showed abnormal cVEMP responses on both sides were significantly greater than those in patients who showed normal cVEMP responses ( P < .05). Conclusion: The vestibulo-spinal reflex mediated by the saccule and its afferents is one of the factors that influence the maintenance of dynamic postural stability as measured by FRT and TUG.